PENGARUH STORE ENVIRONMENT, SHOPPING ENJOYMENT TENDENCY, IMPULSE BUYING TENDENCY TERHADAPIMPULSE BUYING MELALUI POSITIVE AFFECT, NEGATIVE AFFECT, DAN URGE TO BUY IMPULSIVELY PADA SUPERMARKET SUPER INDO MERR SURABAYA - Tresiane Tresiane; Indarini Indarini; Silvia Margaretha (CALYPTRA, 2018)
The Objective of this study is to examine the effect of Store Environment, Shopping Enjoyment Tendency, and Impulse Buying Tendency on Impulse Buying through Positive Affect, Negative Affect, and Urge to Buy Impulsively. Object taken is Super Indo MERR in Surabaya.The data used in this research is primary data obtained from questionnaires. Total respondent are 260 person who have an experience shopping impulsively and minimum 3 times shopping per month. The samling technique of this study was non-probability sampling. This study uses a quantitative approach through statistical analysis, Test conducted using Structural Equation Modeling (SEM) and with the hel of Partial Least Square (PLS) The result of this study show that Store environment have a positive relationship with positive affect and urge to buy impulsively, store environment have a negative relationship with negative affect. Shopping enjoyment tendency have a positive relationship with positive affect, Impulse buying tendency have a positive relationship with urge to buy impulsively. Positive affect have a positive relation with urge to buy impulsively, and urge to buy impulsively have a positive relationship with impulse buying. The relationship between negative affect and urge to buy impulsively proved not to be significant.